Partai Politik, Pemilu, dan Pemerintahan Rusia - Yustiningrum, Emilia (Jurnal Penelitian Politik, 2004)
The changing of Russian domestic politics has been running fast. Many political changings have been caused by the internal push factors that have changed political policies dramatically against the past. The political changing has covered the changing o f political party system from single part\’ into multiparty system. The unpopular election at the national level in the past has been changed into the need to do the election at the national level either to the Parliament's members or the President. The following political changing covered the push to change the role o f government institution to be more structuralized and not centralized anymore into one single position. These domestic political changings were the sign of running to be democratic State. This study has the aim to analyze the historical changing o f Russian domestic politics that has been the basic argument for the future o f political condition.